2014
DOI: 10.5191/jiaee.2014.21304
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ Satisfaction with Extension Services in the Organization of Eastern Caribbean States

Abstract: The economies of most countries in the Organization of Eastern Caribbean States (OECS) are dependent on farming, most of which is done mainly by small farmers in mixed cropping systems. The government is also the main provider of extension services. This study sought to assess farmers' satisfaction with the extensions services and identify areas for improvement. Some 462 farmers in five OECS countries were selected and surveyed in 2013. A farmers' satisfaction index was developed based on 26 statements in a Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 9 publications
(5 reference statements)
3
14
1
1
Order By: Relevance
“…Also contrary to the study [21] found farmers' gender to be linked with Extension service satisfaction and outcomes. In another study [22] revealed that farmers' age, gender and education level significantly influenced farmers' level of satisfaction which was opposite to this study.…”
Section: Relation Between Clienteles' Satisfaction and Independent Vacontrasting
confidence: 93%
“…Also contrary to the study [21] found farmers' gender to be linked with Extension service satisfaction and outcomes. In another study [22] revealed that farmers' age, gender and education level significantly influenced farmers' level of satisfaction which was opposite to this study.…”
Section: Relation Between Clienteles' Satisfaction and Independent Vacontrasting
confidence: 93%
“…Introduction Information Communication Technologies (ICTs) include hardware and software associated with desktop, laptop, and tablet computers, cellular and land-line telephones, radio towers, televisions, DVD players and more (McCole, Culbertson, Suvedi, & McNamara, 2014). ICTs enable Extension officers to respond to audiences faster, disseminate information to larger audiences, and save travel time and expenditures (Ganpat, Webster, & Narine, 2014). Strong, Ganpat, Harder, Irby, and Lindner (2014) suggested that future research should examine new Extension officers' capacity for using ICTs.…”
Section: Conclusion and Futurementioning
confidence: 99%
“…Hence, farmers' access and satisfaction toward agricultural services is a critical factor to gauge the performance of cooperatives. Diversity and quality of the agricultural services are the main indicators for satisfaction (Ganpat et al, 2014). The present study investigates the satisfaction levels of the respondents toward the UACA.…”
Section: Introductionmentioning
confidence: 97%